1994
DOI: 10.1111/j.1472-765x.1994.tb00973.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high hydrostatic pressure on Salmonella thompson and Listeria monocytogenes examined by electron microscopy

Abstract: Cells of Listeria monocytogenes that had been exposed to pressure contained vacuolar regions in the cytoplasm. Pressure‐treated cells of Salmonella thompson contained no vacuoles but had fewer ribosomes than untreated cells and their appearance suggested that some cell lysis had occurred. In both organisms changes in the appearance of the nuclear material were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 6 publications
7
49
1
1
Order By: Relevance
“…The intracellular regions of low density observed in L. lactis (Fig. 2) are similar to those observed in pressure-treated L. monocytogenes by Mackey et al (18). These authors suggest that the low-density regions are caused by transient membrane invaginations under pressure that are subsequently reversed upon pressure release, leaving the low-density regions adjacent to the cell membrane.…”
Section: Discussionsupporting
confidence: 70%
“…The intracellular regions of low density observed in L. lactis (Fig. 2) are similar to those observed in pressure-treated L. monocytogenes by Mackey et al (18). These authors suggest that the low-density regions are caused by transient membrane invaginations under pressure that are subsequently reversed upon pressure release, leaving the low-density regions adjacent to the cell membrane.…”
Section: Discussionsupporting
confidence: 70%
“…The condensed nucleoids of pressure-treated cells were often irregularly positioned within the cell, unlike those seen in chloramphenicol-treated cells, which are generally rather symmetrical and central to the cell axis. This asymmetric appearance has also been observed with pressure-treated cells of S. enterica serovar Thompson examined by electron microscopy (20). Condensation of the nucleoid was also observed for the gram-positive organisms Listeria monocytogenes and Lactobacillus plantarum (20,39).…”
Section: Discussionmentioning
confidence: 50%
“…However, it has also been reported that in some cases, pressure-killed stationary-phase cells retain a functional membrane (24), and this has led to the consideration of other structures inside the cell as potential key targets for inactivation. Some authors have reported similarities between cell inactivation and protein denaturation kinetics (19,36), and changes in the conformation of various structures in the bacterial cell, such as the nucleoid and ribosomes, have been reported for electron microscopy and differential scanning calorimetry studies (20,23,26). However, it is still not clear which, if any, of these changes is responsible for the inactivation of the cell.…”
mentioning
confidence: 99%
“…In all cases, the integrity of the cytoplasmic membrane was apparently maintained. The types of physical damage observed by electron microscopy in this study were both different and less severe than those observed for other treatments, such as freezing and exposure to lysozyme or high pressure (El-Kest and Marth 1992;Mackey et al 1994). Even the presence of a preservative such as potassium sorbate appeared to have little visible effect on cells during chill-storage.…”
Section: Discussionmentioning
confidence: 70%